The Effects of Insecure Attachment Style on Workplace Deviance: A Moderated Mediation Analysis - Ye, Weijiao; Zhao, Huijun; Song, Xiaoxiao; Li, Ziqiang; Liang, Jingxuan (Frontiers in Psychology, 2022)
The purpose of this study is to explore why workplace deviance behavior among employees has increased during Corona Virus Disease 2019 (COVID-19) from the perspective of insecure attachment style. Based on attachment theory, we propose and test the effect of insecure attachment style (attachment anxiety, attachment avoidance) on deviance behavior (organizational deviance behavior, interpersonal deviance behavior) via organization-based self-esteem using 422 data from Chinese employees. And we further examine the moderating role of leader-member exchange in reducing workplace deviance behavior. The findings show that attachment anxiety and attachment avoidance are both positively related to workplace deviance behavior. Attachment anxiety and attachment avoidance both indirectly predict organizational deviance behavior through organization-based self-esteem. Moreover, leader-member exchange can moderate the indirect effects of both attachment anxiety and attachment avoidance on organizational deviance behavior via organization-based self-esteem. This research highlights the fact that employees with insecure attachment style need more care from the organization during the COVID-19 pandemic and demonstrates that one of the key ways in which insecure attachment style increases organization-based self-esteem is by facilitating the development of high-quality leader-member exchange.